AN EMPIRICAL EVALUATION OF PUBLIC SECONDARY SCHOOLS’ EDUCATION FINANCING AND ITS IMPACT ON SERVICE QUALITY IN LUSAKA, ZAMBIA - Hapompwe, Chrine C.; Karim, FCGIA, Prof. Dr. Asif Mahbub; Kambikambi, Ph.D, Dr. Tamala-Tonga (African Journal of Education and Practice, 2020)
Purpose: This study was envisaged to empirically evaluate the impact of public secondary schools' education financing on service quality in Lusaka district of the Republic of Zambia. Methodology: As an impact study, it employed a triangulation incorporating a causal-analytical paradigm targeting 34 public secondary schools in Lusaka district with over 60,000 pupils and about 2,000 teachers as population (N). A census method was used with 170 structured questionnaires being distributed to five persons per school who constitute the school management structure while 3 focus group discussions of 10 each were held among senior pupils, teachers and head teachers coupled with key informant interviews with district official, MoGE HQ official and donors' representative through appointment and prior clearance as procedures. Simple random and purposive sampling techniques were used with primary and secondary data being obtained and analysed via thematic / content approaches for qualitative and SPSS / excel for quantitative data along with expert judgement. The study had questionnaire return rate of 84% (143). Findings: The study established that the MoGE sector's financing from central government from 2015 to 2019 had been steadily declining from 20.2% in 2015 to 15.1% in 2019, against the global standard annual benchmark of 20%. The impact of the phenomena was obliteration of investments in school construction / classroom expansion, school supplies and human resources. Moreover, quantitative field findings indicated abnormal teacher to pupil ratios of 1: 70, pupil to computer ratios of 2:1, double-seater desk to pupil ratios of 1:3, English text book to pupil ratios of 1:3, Science text book to pupil ratios of 1:6, Biology text book to pupil ratios of 1:5, none availability of libraries and library stocks, average shortages of 5 teachers per school, overloads of up to 45 periods per teacher instead of 24, existence of unqualified teachers, reduced learner contact hours, compromised formative assessments and reduced school inspections. Besides, the study ascertained the existence of financial inadequacies in the system arising from its procurement bureaucratic nature as resources for subsector inputs had severally been either misapplied or misappropriated. Mismanagement of these resources was positively correlated with some prominent donors' withdrawal of their pool fund budgetary support to the education sector. This withdrawal of financing coupled with the country's bulging public debt stock (of over US 11 billion) have been established as frontline attributive factors to the dwindling financing to the education sector with implicative spill over negative effects to its subsector to the effect that whereas accessibility and affordability might have been guaranteed by top-down policy directives and imperatives, service quality has been severely compromised and the learner achievements during the period under review have stagnated at averages of 65.8% at grade 12 level and 75.6% at grade 9 level. Unique contribution: The study strongly implores central government through the MoGE to take thematically objective and pragmatic policy measures to curtail the phenomena by prioritizing the education sector in public financing, sealing the sector's financial loopholes, and restoring the lost confidence of some prominent donors consistent with the ideals and principles of the human capital and optimal resource theories.